Prophetic divination essays in ancient near eastern prophecy - Nissinen, Martti 1959- (Berlin Boston De Gruyter, 2019)
Frontmatter -- Preface -- List of Original Publications -- List of Abbreviations -- Table of Contents -- Part One: Prophecy in Theory -- Prophecy as Construct, Ancient and Modern -- Reflections on the “Historical-Critical” Method: Historical Criticism and Critical Historicism -- What is Prophecy? An Ancient Near Eastern Perspective -- Prophecy and Omen Divination: Two Sides of the Same Coin -- Neither Prophecies nor Apocalypses: The Akkadian Literary Predictive Texts -- Part Two: Prophecy in the Ancient Near East -- The Socioreligious Role of the Neo-Assyrian Prophets -- Non-Male Prophets in Ancient Near Eastern Sources -- The Prophet and the Augur at Tušḫan, 611 BCE -- Das kritische Potential in der altorientalischen Prophetie -- Fear Not: A Study on an Ancient Near Eastern Phrase -- The Exiled Gods of Babylon in Neo-Assyrian Prophecy -- Marduk’s Return and Reconciliation in a Prophetic Letter from Arbela (with Simo Parpola) -- City as Lofty as Heaven: Arbela and Other Cities in Neo-Assyrian Prophecy -- A Prophetic Riot in Babylonia, 133 BCE -- Part Three: Biblical Prophecy in Ancient Near Eastern Context -- Die Relevanz der neuassyrischen Prophetie für die alttestamentliche Forschung -- Biblical Prophecy from a Near Eastern Perspective: The Cases of Kingship and Divine Possession -- Comparing Prophetic Sources: Principles and a Test Case -- From Holy War to Holy Peace: Biblical Alternatives to Belligerent Rhetoric -- Falsche Prophetie in neuassyrischer und deuteronomistischer Darstellung -- Sacred Springs and Liminal Rivers: Water and Prophecy in the Ancient Eastern Mediterranean -- Prophets and the Divine Council -- Wisdom as Mediatrix in Sirach 24: Ben Sira, Love Lyrics, and Prophecy -- Part Four: Prophecy in the Hebrew Bible -- The Historical Dilemma of Biblical Prophetic Studies -- Since When Do Prophets Write? -- Prophets and Prophecy in Joshua–Kings: A Near Eastern Perspective -- Das Problem der Prophetenschüler -- The Dubious Image of Prophecy -- (How) Does the Book of Ezekiel Reveal Its Babylonian Context? -- The Book of Hosea and the Last Days of the Northern Kingdom: The Methodological Problem -- Part Five: Prophecy in the Dead Sea Scrolls -- Transmitting Divine Mysteries: The Prophetic Role of Wisdom Teachers in the Dead Sea Scrolls -- Oracles at Qumran? Traces of Inspired Speakers in the Dead Sea Scrolls -- Pesharim as Divination: Qumran Exegesis, Omen Interpretation and Literary Prophecy -- Bibliography -- Index of Names -- Index of modern authors -- Index of Ancient Near Eastern Sources -- Index of Biblical References
Prophecy was a wide-spread phenomenon in the ancient world - not only in ancient Israel but in the whole Eastern Mediterranean cultural sphere. This is demonstrated by documents from the ancient Near East, that have been the object of Martti Nissinen’s research for more than twenty years. Nissinen's studies have had a formative influence on the study of the prophetic phenomenon. The present volume presents a selection of thirty-one essays, bringing together essential aspects of prophetic divination in the ancient Near East. The first section of the volume discusses prophecy from theoretical perspectives. The second sections contains studies on prophecy in texts from Mari and Assyria and other cuneiform sources. The third section discusses biblical prophecy in its ancient Near Eastern context, while the fourth section focuses on prophets and prophecy in the Hebrew Bible/Old Testament. Even prophecy in the Dead Sea Scrolls is discussed in the fifth section. The articles are essential reading for anyone studying ancient prophetic phenomenon
In English
Keywords: Prophecy -- Comparative studies; Prophecy -- History; Prophets -- Middle East -- History; Semites -- Religion; RELIGION / Biblical Criticism & Interpretation / Old Testament; Divination; Hebrew Bible; History of Religion; Prophecy; Aufsatzsammlung